3y-4+y+18=8y+20-6y

Simple and best practice solution for 3y-4+y+18=8y+20-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-4+y+18=8y+20-6y equation:


Simplifying
3y + -4 + y + 18 = 8y + 20 + -6y

Reorder the terms:
-4 + 18 + 3y + y = 8y + 20 + -6y

Combine like terms: -4 + 18 = 14
14 + 3y + y = 8y + 20 + -6y

Combine like terms: 3y + y = 4y
14 + 4y = 8y + 20 + -6y

Reorder the terms:
14 + 4y = 20 + 8y + -6y

Combine like terms: 8y + -6y = 2y
14 + 4y = 20 + 2y

Solving
14 + 4y = 20 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
14 + 4y + -2y = 20 + 2y + -2y

Combine like terms: 4y + -2y = 2y
14 + 2y = 20 + 2y + -2y

Combine like terms: 2y + -2y = 0
14 + 2y = 20 + 0
14 + 2y = 20

Add '-14' to each side of the equation.
14 + -14 + 2y = 20 + -14

Combine like terms: 14 + -14 = 0
0 + 2y = 20 + -14
2y = 20 + -14

Combine like terms: 20 + -14 = 6
2y = 6

Divide each side by '2'.
y = 3

Simplifying
y = 3

See similar equations:

| 9c+15c^3=0 | | 1000.00+500000x=1350.00 | | 20=13y-8y | | -84=-7(8-4K) | | 8y-12-3y=-2 | | 9x+8y=-16 | | 4(4x-3)=8(2x-2)+4 | | 9n-20=7 | | 6x-10=3x+5 | | 42y-7=31 | | 54=4w+2w | | 90×2/3 | | M^2+56=15m | | 54=4w | | x-3=-2+3 | | 2*x+3=5*x+17 | | 5(n-1)=55 | | 3x+5.4=(-6.3) | | 8x+y=240 | | 5y-17=-2 | | 5x/5y | | 10+11y+3y^2=0 | | 8-x=-2x+16 | | 6x+9=-6x-81 | | 2x^2+15x-2=0 | | a=17-b | | f(11)=2(11)+4 | | N/3-8=16 | | 8x+9y=96 | | f(11)=2x+4 | | (3^×)(9^2x)=1^3/9 | | y=0.25x+8 |

Equations solver categories